Photovoltaics rooftop regulations and their connection to pro-environment consumer behavior in Indonesia - Appin Purisky Redaputri; Claudius Budi Santoso; M Yusuf S Barusman (Center for Science and Technology, IAIN Surakarta, 2024)
To address environmental issues, Indonesia aims to achieve a 23% renewable energy share by 2025 and 31% by 2050, according to the National Energy Plan. This article examines the regulations governing the management of rooftop solar power plant (rooftop-PV) in Indonesia and their connection to pro-environment consumer behavior. Despite Indonesia’s ambitious targets for Renewable Energy (RE) growth, progress in the field still needs improvement. Pro-environmental behavior (PEB) within the community is crucial for adopting rooftop PV as a more environmentally friendly energy alternative. This research employs a qualitative descriptive methodology with content analysis to evaluate the current situation. The research findings indicate that rooftop PV offers economic benefits through cost savings for consumers and is supported by existing regulations. However, some businesses feel that the government needs to expedite revising relevant regulations to address investment stagnation and installed solar panel capacity. Concerns arise that proposed policy changes may hinder the growth of rooftop PV businesses and the achievement of national capacity targets. The role of pro-environment consumer behavior, which has the potential to drive rooftop PV adoption, will be influenced by psychological and social factors, as well as changes in applicable regulations.